2020
DOI: 10.1016/j.heliyon.2019.e03086
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-based training for flexible cystoscopy – A randomized trial comparing two approaches

Abstract: Background: Simulation-based training allows trainees to experiment during training and end-of-training tests could increase motivation and retention. The aim of this trial was to determine if a simulation-based training program including directed self-regulated learning and post-testing improved clinical outcomes compared to a traditional simulation-based training program.Methods: A randomized trial was conducted involving 32 participants without prior experience in endoscopic procedures. The intervention gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The studies included first year to sixth year medical students and were published between 2001 and 2020. In terms of the topic or area of study, 53% (34/64) of the studies focused on laparoscopic surgery [ 22 , 24 , 27 , 31 , 35 - 38 , 40 , 41 , 45 - 48 , 50 - 52 , 54 , 56 - 66 , 69 , 78 , 81 - 83 ]; 16% (10/64) on surgery [ 25 , 28 , 53 , 55 , 67 , 68 , 71 , 74 , 76 , 77 ]; 8% (5/64) on orthopedic surgery [ 39 , 42 , 73 , 79 , 84 ]; 8% (5/64) on ureteroscopy [ 30 , 33 , 34 , 80 , 85 ]; 5% (3/64) each on ophthalmology [ 26 , 70 , 75 ] and intravenous cannulation [ 29 , 32 , 72 ], and 2% (1/64) each on endoscopy [ 49 ], colonoscopy [ 23 ], shoulder-joint clinical anatomy [ 44 ], and empathic communication skills [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies included first year to sixth year medical students and were published between 2001 and 2020. In terms of the topic or area of study, 53% (34/64) of the studies focused on laparoscopic surgery [ 22 , 24 , 27 , 31 , 35 - 38 , 40 , 41 , 45 - 48 , 50 - 52 , 54 , 56 - 66 , 69 , 78 , 81 - 83 ]; 16% (10/64) on surgery [ 25 , 28 , 53 , 55 , 67 , 68 , 71 , 74 , 76 , 77 ]; 8% (5/64) on orthopedic surgery [ 39 , 42 , 73 , 79 , 84 ]; 8% (5/64) on ureteroscopy [ 30 , 33 , 34 , 80 , 85 ]; 5% (3/64) each on ophthalmology [ 26 , 70 , 75 ] and intravenous cannulation [ 29 , 32 , 72 ], and 2% (1/64) each on endoscopy [ 49 ], colonoscopy [ 23 ], shoulder-joint clinical anatomy [ 44 ], and empathic communication skills [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 62 studies that reported on participants’ postintervention skills, 11 (18%) reported change score from baseline for the skills outcome [ 25 , 50 , 56 , 58 , 68 , 73 , 76 - 78 , 80 , 85 ] and 1 (2%) reported change score from baseline for the satisfaction outcome [ 68 ]. Regarding retention, 7.8% (5/64) of the studies assessed skills retention at 2-4 weeks after the intervention [ 25 , 31 , 33 , 40 , 83 ]. The remaining studies did not report retention outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…In this phase of the selection process 405 records were excluded. The full-texts of the remaining 37 records were assessed for eligibility and 23 records were excluded with the following reasons: 12 records reported an intervention, which was not eligible for inclusion ( Bode et al, 2012 ; Bube, Konge & Hansen, 2017 ; Craven et al, 2018 ; Custers et al, 1999 ; Handley & Handley, 1998 ; Hill et al, 2010 ; Holmes et al, 1998 ; Krautter et al, 2015 ; Liu & Hunt, 2017 ; Velmahos et al, 2004 ; Wirth et al, 2018 ; Yoganathan et al, 2018 ); 8 records used a study design, which was not eligible for inclusion ( Easton, Stratford-Martin & Atherton, 2012 ; Mishra & Dornan, 2003 ; Nikendei et al, 2014 ; Schroder et al, 2017 ; Skrzypek et al, 2018 ; Smith et al, 2019 ; Sopka et al, 2012 ; Tommaso, 2016 ); 2 records were excluded because of missing data ( Archer, Van Hoving & De Villiers, 2015 ; Seymour-Walsh et al, 2015 ) and 1 record did not use the specified primary outcome assessment for procedural skills ( Greif et al, 2010 ). Finally, 14 studies were included into this systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that we are not exclusively suggesting a ML approach for all procedures; an appropriate pedagogical framework should be linked to the underlying objectives. There is, however, emerging evidence that clinical outcomes between SBPT using traditional instruction compared with demonstration and unsupervised independent practice are not significantly different suggesting a ML approach would be best suited for all procedure-based training to keep learning in line with explicit standards [ 45 ]. Instructional design and deliberate practice (DP) are core components of ML that aid the practical implementation of the framework [ 46 , 47 ] centred around upskilling individuals to a desired standard with task-specific feedback, facilitated by use of a checklist.…”
Section: Sbpt Blueprintmentioning
confidence: 99%